Влияние канальных и аппаратурных коррелированных помех на погрешность частотно-временной синхронизации - Коваль, Ю. А.; Иванова, Е. А.; Приймак, В. Ю.; Ал-Твежри, Б. А. (ХНУРЭ, 2011)
The results of theoretical analysis, simulation studie of little-known deviations of delays in the AFD from the ideal values. Such anomalous delays must be considered in systems with high-precision measurement of signal time positions.
Keywords: частотно-временная синхронизация; пеленгация; высокоточное измерение сигналов